Dataset about the adoption of winter cover crops at the municipality level for mainland France - Benjamin Nowak; Audrey Michaud; Gaëlle Marliac (Data in Brief, 2022)
Winter soil cover by vegetation is associated with multiple benefits, such as increasing soil carbon storage and reducing erosion and nutrient leaching. This dataset provides an estimate of winter soil cover before spring-sown crops at municipality level for mainland France for two years (2018 and 2019). These estimates were obtained through the monitoring of all plots with spring-sown crops, declared within the context of the European Common Agricultural Policy. Detection of plots with winter soil cover was achieved through the analysis of Normalized Difference Vegetation Index (NDVI) time series, computed from Sentinel-2 multispectral images.For this dataset, it was considered that soil cover had to exceed 50% for a plot to be considered as covered by vegetation. Based on the literature, this corresponds to a threshold NDVI value between 0.45 and 0.59. To allow for sensitivity and uncertainty analyses for future studies that may be conducted using these data, three estimates of winter soil cover are given: minimum (based on the cultivated area exceeding the upper NDVI threshold of 0.59), maximum (considering the lower NDVI threshold of 0.45) and best estimate (mean NDVI threshold of 0.52). This dataset may be useful primarily to researchers working on biogeochemical cycle modeling or to government agencies, as several public policies (such as the Nitrates Directive) aim at developing winter cover crops.